FORMULASI ES KRIM SARI KURMA - Cesia Agustin (JURNAL RISET KESEHATAN POLTEKKES DEPKES BANDUNG, Online ISSN 2579-8103, 2018)
ABSTRACT : Dengue is one of health problems in Indonesia. Usually, dengue sufferers will decrease the body stamina responses. One of the nutrient substances which can increase thrombopoitein is omega 6 or linoleic acid in dates extract. This research is using experimental stufy, with samples as many as 30 panellist who filled hedonic test worksheet. The collected data are colour, taste, aroma and texture. Ice cream with dates extract which is liked most from colour side is formula 366, from taste side is formula 455, from aroma side is formula 904, and from texture side is formula 455. So, the product that is chosen most is formula 455, because it is liked from taste and texture side. According to the result of the research, ice cream with dates extract product shoul be repaired both in colour and aroma side in formulation 366 and 904, and need to conduct an advance research to dengue sufferers who are given ice cream with dates extract.